The impact of epiphytic algae on the foliar traits of Potamogeton perfoliatus - Viktor R. Tóth (Frontiers in Plant Science)
This study investigated the effect of epiphyton on foliar traits of a submerged rooted macrophyte, Potamogeton perfoliatus, in a shallow freshwater lake, highlighting its influence on the ecological dynamics of littoral zones in aquatic ecosystems. It was shown that the limnological characteristics of the sampling sites (water chlorophyll-a, total suspended matter and coloured dissolved organic matter content) had no significant effect on the average values of epiphytic algal content found on pondweed leaves, while influencing the plasticity of these data. The responses of morphological and physiological traits of submerged macrophytes to accumulated epiphyton demonstrate the complexity of their relationship: epiphyton colonisation had no relevant effect on leaf morphology (except leaf length) and leaf pigment content (except Chl-a/Chl-b ratio), however, this study highlights the significant influence of epiphytic algal biomass on photophysiological traits of submerged macrophyte leaves, as 5 out of 6 photophysiological traits were affected. The results highlight the importance of considering epiphyte colonisation when seeking to understand the ecological functioning of littoral aquatic ecosystems. Furthermore, the complex interactions between epiphytes and submerged rooted macrophytes should be considered in integrated lake management and environmental protection policies. These interactions play an important, though ambiguous role in shaping habitat variability and overall ecosystem health in littoral zones.